Overview of the Instructor Professional Certification Scheme - Bahri, Efri Syamsul (Journal of Multi-Disciplines Science, 2024)
Instructors have a strategic role in developing superior human resources in Indonesia. This research aims to identify the Instructor Professional Certification Scheme in the Qualification Level category in the Field of Job Training and Certification in the Instructor Group Job Training Subfield. This study uses a qualitative method. The research approach was carried out descriptively and by literature study. Data comes from reference journal articles and regulations related to Instructors. Data was analyzed descriptively to explain the Instructor Professional Certification Scheme. This research found that the Qualification Levels in the Field of Job Training and Certification in the Instructor Group Job Training Subfield refer to the Decree of the Minister of Manpower of the Republic of Indonesia No. 3 of 2021. These Qualification Levels start from Qualifications 3 to 6. The government needs to provide support to increase the number of competent instructors.